2006
DOI: 10.1038/nrm1890
|View full text |Cite
|
Sign up to set email alerts
|

Local force and geometry sensing regulate cell functions

Abstract: The shapes of eukaryotic cells and ultimately the organisms that they form are defined by cycles of mechanosensing, mechanotransduction and mechanoresponse. Local sensing of force or geometry is transduced into biochemical signals that result in cell responses even for complex mechanical parameters such as substrate rigidity and cell-level form. These responses regulate cell growth, differentiation, shape changes and cell death. Recent tissue scaffolds that have been engineered at the micro- and nanoscale leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
1,656
3
11

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 2,090 publications
(1,697 citation statements)
references
References 159 publications
27
1,656
3
11
Order By: Relevance
“…(Baneyx et al 2002;Mao and Schwarzbauer 2005;Abu-Lail et al 2006) This elasticity appears to come from unfolding domains of fibronectin and shifting to extended molecular conformations. (Baneyx et al 2002;Abu-Lail et al 2006;Vogel and Sheetz 2006) As discussed later, mechanical stretching of TM cells and their ECMs triggers homeostatic responses that reduce the outflow resistance. These fibronectin fibrils, which would have a number of cellular integrin attachments for each fibril, would provide an ideal sensing structure to communicate IOP-induced mechanical stretch to TM cells.…”
Section: Fibronectin and Vitronectinmentioning
confidence: 99%
“…(Baneyx et al 2002;Mao and Schwarzbauer 2005;Abu-Lail et al 2006) This elasticity appears to come from unfolding domains of fibronectin and shifting to extended molecular conformations. (Baneyx et al 2002;Abu-Lail et al 2006;Vogel and Sheetz 2006) As discussed later, mechanical stretching of TM cells and their ECMs triggers homeostatic responses that reduce the outflow resistance. These fibronectin fibrils, which would have a number of cellular integrin attachments for each fibril, would provide an ideal sensing structure to communicate IOP-induced mechanical stretch to TM cells.…”
Section: Fibronectin and Vitronectinmentioning
confidence: 99%
“…The relationship of cell adhesion and motility to the substrate stiffness has become the focus of major studies in recent years (Bershadsky et al, 2006;Geiger and Bershadsky, 2001;Georges and Janmey, 2005;Rehfeldt et al, 2007;Vogel and Sheetz, 2006). It has been found that force sensing and substrate stiffness define the formation and turnover of the adhesions to the extracellular matrix and determine the speed of migration, as well as cell shape and ability to differentiate (Engler et al, 2006).…”
Section: Extracellular Matrix and Force Sensing: Paving The Pathways mentioning
confidence: 99%
“…In addition to soluble biochemical cues such as growth factors and cytokines, cells are also known to sense and respond to physical factors, including the mechanical properties of their environment (as reviewed in Discher et al, 2005;Ingber, 2006;Vogel and Sheetz, 2006) and the local topography of their substrates (Dalby et al, 2004;Dalby et al, 2005). Differences in substrate rigidity (Engler et al, 2006;Galbraith et al, 2002;Giannone and Sheetz, 2006;Kostic and Sheetz, 2006;Yeung et al, 2005) as well as micro-and nanoscale features (Dalby et al, 2005) have been correlated with profound effects on cell adhesion, morphology, proliferation, and gene regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the underlying molecular mechanisms by which physical factors, including force and the mechanical properties of matrices, are converted into biochemical signals that ultimately regulate protein expression are only beginning to be explored (Kostic and Sheetz, 2006). One focus is to identify proteins whose structure/function relationship can be altered by mechanical forces, causing for example the opening of ion channels, a change in the spatial presentation of binding sites, or the exposure of otherwise cryptic binding sites (for reviews see Bustamante et al, 2004;Kung, 2005;Vogel, 2006;Vogel and Sheetz, 2006;Arcangeli and Becchetti, 2006).…”
Section: Introductionmentioning
confidence: 99%